2016
DOI: 10.1142/s0218301316420064
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-ion physics at the LHC: Review of Run I results

Abstract: In this work we review what we consider are, some of the most relevant results of heavy-ion physics at the LHC. This paper is not intended to cover all the many important results of the experiments, instead we present a brief overview of the current status on the characterization of the hot and dense QCD medium produced in the heavy-ion collisions. Recent exciting results which are still under debate are discussed too, leading to intriguing questions like whether we have a real or fake QGP formation in small s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 148 publications
(114 reference statements)
2
15
0
Order By: Relevance
“…Recent results on particle production at the LHC obtained in high-multiplicity proton-proton (pp) and proton-lead (p-Pb) collisions revealed phenomena which are similar to those seen in Pb-Pb collisions where they are attributed to bulk collective effects [1,2]. Apart from the peculiar patterns seen in two-particle azimuthal correlations [3,4], notably, some of these observations are the radial flow signals [5,6] and the strangeness enhancement [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…Recent results on particle production at the LHC obtained in high-multiplicity proton-proton (pp) and proton-lead (p-Pb) collisions revealed phenomena which are similar to those seen in Pb-Pb collisions where they are attributed to bulk collective effects [1,2]. Apart from the peculiar patterns seen in two-particle azimuthal correlations [3,4], notably, some of these observations are the radial flow signals [5,6] and the strangeness enhancement [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…Probes of the QGP phase had been found by large experimental efforts at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC) [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship with the QCD phase diagram can be derived in terms of the thermodynamical quantities [3]. In these manuscript we extend the results to study the signatures of collective effects which has been shown on recent results on p-p and p-Pb (small systems) collisions measured by the collaborations ALICE, CMS and ATLAS at LHC energies [4] [5], and which origin is still not fully understand.…”
Section: Introductionmentioning
confidence: 65%